2020
DOI: 10.2147/copd.s279293
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long-Term Effects of Pedometer-Based Physical Activity Coaching in Severe COPD: A Randomized Controlled Trial</p>

Abstract: Background and Objective: Limited evidence on long-term effects of physical activity programs in COPD is available. The aim of the study was to investigate the effects of a threemonth program combining physical activity counselling and pedometer-based feedback in addition to usual care, followed by a nine-month unsupervised observation period as compared to usual care in participants with severe to very severe COPD. Methods: Participants were randomized to either a control group receiving usual care or an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…While this provides evidence regarding the short-term benefits of a step-based intervention in this population, between-group differences in PA were no longer significant 12-to 16-weeks post-intervention, indicating that the intervention did not lead to a sustained improvement in PA behaviour. These findings mirror the evidence for the short- 34 versus long-term effectiveness 35 of pedometer-based interventions in increasing PA in the chronic obstructive pulmonary disease (COPD) population. In COPD, it has been suggested that multidimensional and possibly repeated intervention targeting not only PA but also exercise capacity and HRQoL may be needed to achieve sustained improvements in PA 35 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…While this provides evidence regarding the short-term benefits of a step-based intervention in this population, between-group differences in PA were no longer significant 12-to 16-weeks post-intervention, indicating that the intervention did not lead to a sustained improvement in PA behaviour. These findings mirror the evidence for the short- 34 versus long-term effectiveness 35 of pedometer-based interventions in increasing PA in the chronic obstructive pulmonary disease (COPD) population. In COPD, it has been suggested that multidimensional and possibly repeated intervention targeting not only PA but also exercise capacity and HRQoL may be needed to achieve sustained improvements in PA 35 .…”
Section: Discussionsupporting
confidence: 61%
“…These findings mirror the evidence for the short- 34 versus long-term effectiveness 35 of pedometer-based interventions in increasing PA in the chronic obstructive pulmonary disease (COPD) population. In COPD, it has been suggested that multidimensional and possibly repeated intervention targeting not only PA but also exercise capacity and HRQoL may be needed to achieve sustained improvements in PA 35 . Whether a similar approach is required in the severe asthma population warrants further investigation.…”
Section: Discussionsupporting
confidence: 61%
“…This is a secondary outcome analysis from a single-centre parallel group, randomised controlled trial [25].…”
Section: Methodsmentioning
confidence: 99%
“…Data was collected between May 2017 and May 2020. This study describes the analysis of the secondary outcome from a randomised controlled trial (RCT) investigating the effects of a combined PA counselling and pedometer-based feedback intervention in severe and very severe COPD [25]. Patients aged 40 years or older with diagnosed severe and very severe COPD (i.e.…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation